Work From Home Terhadap Kinerja Karyawan Pada Masa Pandemi Covid 19 - Adi Hartono; Dedi Rianto Rahadi (Jurnal Manajemen dan Bisnis, 2021)
During this pandemic period, of course, there are very significant changes in many fields. One of them is in the economic sector, with this pandemic, almost all companies have made changes in their activities. One of the company's activities in responding to this pandemic is by conducting WFH (Work From Home). In a company, of course the most influential resource is the human resource. The success of the company in carrying out its activities is influenced by the performance of the company's employees. The author takes the object of the employees PT. Sayap Mas Utama. Therefore, the authors conducted a study to determine the performance of employees employed at home during the Covid 19 pandemic. The method used by the author is a qualitative method, namely by interviewing informants to obtain the information needed in this study. The results and analysis obtained from this study and the conclusions obtained are that the performance of employees who were employed at home during this pandemic period decreased their work performance significantly.